A Maqāṣid al-Sharīʿah Analysis of the Indonesian Ulema Council's Fatwa on Interfaith Greetings within Contemporary Human Rights Discourse - Ahmad Musadad; Achmad Badarus Syamsi; Sibawaihi Sibawaihi; Holis Holis; Tri Pujiati; Anis Wahdati; Afaful Ummah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
The Indonesian Ulema Council's (MUI) fatwa on interfaith greetings has generated significant debate within Indonesia's religious and socio-legal landscape, particularly regarding its implications for pluralism and interreligious harmony. This study conducts a Maqāṣid al-Sharīʿah–based analysis of the fatwa within the broader discourse of contemporary human rights. Using a qualitative textual approach, it examines how the fatwa articulates the objectives of Islamic Law (maqāṣid), especially in balancing the protection of faith (ḥifẓ al-dīn) with the demands of social cohesion in a religiously diverse society. The analysis is positioned in dialogue with contemporary human rights norms, drawing selectively on the Universal Declaration of Human Rights (UDHR) and the Cairo Declaration on Human Rights in Islam (CDHRI) to contextualise the fatwa's normative orientation. The findings indicate that while Western human rights discourse tends to emphasise individual autonomy, freedom of expression, and the neutrality of religious symbols, Islamic human rights frameworks foreground the primacy of Sharīʿah in regulating religious interactions. Within this normative landscape, the MUI fatwa seeks to preserve core Islamic values while acknowledging the importance of maintaining respectful interfaith relations in a pluralistic society. Academically, this study contributes to current scholarship by demonstrating how Maqāṣid al-Sharīʿah can serve as a mediating analytical framework between Islamic legal reasoning and global human rights discourse. It offers a more nuanced understanding of how fatwas function not merely as legal pronouncements but also as instruments of socio-religious negotiation in multicultural contexts. Moreover, the study provides a conceptual bridge for integrating maqāṣid-based reasoning into contemporary discussions of religious freedom, tolerance, and interfaith engagement, highlighting the potential of Islamic legal theory to enrich broader human rights conversations constructively in Muslim-majority societies.